2001
DOI: 10.1002/cne.1395
|View full text |Cite
|
Sign up to set email alerts
|

Development and connectivity of olfactory pathways in the brain of the lobster Homarus americanus

Abstract: The main output pathways from the olfactory lobes (primary olfactory centers) and accessory lobes (higher-order integrative areas) of decapod crustaceans terminate within both of the main neuropil regions of the lateral protocerebrum: the medulla terminalis and the hemiellipsoid body. The present study examines the morphogenesis of the lateral protocerebral neuropils of the lobster, Homarus americanus, and the development of their neuronal connections with the paired olfactory and accessory lobes. The medulla … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 79 publications
(129 reference statements)
0
21
0
Order By: Relevance
“…Although it has not been demonstrated experimentally, the non-aesthetasc pathway may detect spatial aspects of an odor stimulus through the integration of chemosensory and mechanosensory cues. The fact that the output interneurons from the lateral antennular neuropils and from the olfactory lobes project to distinctly different regions of the protocerebrum (Sullivan and Beltz, 2001) supports the notion that these pathways have some divergent functions.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Although it has not been demonstrated experimentally, the non-aesthetasc pathway may detect spatial aspects of an odor stimulus through the integration of chemosensory and mechanosensory cues. The fact that the output interneurons from the lateral antennular neuropils and from the olfactory lobes project to distinctly different regions of the protocerebrum (Sullivan and Beltz, 2001) supports the notion that these pathways have some divergent functions.…”
mentioning
confidence: 69%
“…Output interneurons from the olfactory lobes and from the lateral antennular neuropil project to different regions of the terminal medullae (Sullivan and Beltz, 2001). It should be noted, however, that there is some connectivity between these two neuropils; for example, local olfactory interneurons exist that connect the ipsilateral olfactory lobe and lateral antennular neuropil (Mellon and Alones, 1994;Schmidt and Ache, 1996b (D-F) High-resolution scanning electron micrographs of three bimodal chemomechanosensilla: (D) hooded sensillum, (E) medium simple sensillum and (F) long simple sensillum.…”
mentioning
confidence: 99%
“…The importance of the lateral protocerebrum in the olfactory pathway has also been underlined by ablation experiments suggesting that this region is involved in discriminating food from nonfood items and in the control of feeding behaviors (Maynard and Dingle, 1963;Maynard and Yager, 1968;Maynard and Sallee, 1970;Hazlett, 1971). In addition to having strong connections with the olfactory lobe, the lateral protocerebrum also has connections with the optic neuropils (Hanström, 1925;Mellon, 2000;Sullivan and Beltz, 2001b) and is therefore thought to be an associative brain center.…”
Section: Indexing Terms: Accessory Lobe; Olfactory Pathway; Olfactorymentioning
confidence: 94%
“…They then project to distinct neuropil structures in the lateral protocerebrum, the hemiellipsoid body and the medulla terminalis where integration with visual input and, most likely, also mechanosensory input, takes place (Mellon and Alones 1993, Sandeman and Sandeman 1994, Sandeman et al 1995a, b, Sullivan and Beltz 2001a. Although neuroanatomical and physiological aspects of this important neuronal pathway that is so characteristic for the crustacean brain are being intensely analysed (e. g., Mellon et al 1992a, b, Mellon and Alones 1993, Sandeman and Sandeman 1994, Wachowiak and Ache 1994, Schmidt and Ache 1997, Wachowiak et al 1997, Mellon 2002, Sullivan and Beltz 2001a, b, McKinzie et al 2003, Sullivan and Beltz 2005a, the neurotransmitter of the projection neurons has nevertheless been unknown for many years. However, studies on the crayfish P. clarkii (Yasuda et al 2004, Yasuda-Kamatani and Yasuda 2006, Sullivan et al 2007 and Cherax destructor (Sullivan and Beltz 2005b) have indicated that a recently identified neuropeptide, crustacean-SIFamide (GYRKPPF NGSIFamide), is a major neurotransmitter of these projection neurons.…”
Section: Introductionmentioning
confidence: 99%